2019
DOI: 10.1002/anie.201812954
|View full text |Cite
|
Sign up to set email alerts
|

Nylon Intermediates from Bio‐Based Levulinic Acid

Abstract: Use of ZrO 2 /SiO 2 as asolid acid catalyst in the ringopening of biobased g-valerolactone with methanol in the gas phase leads to mixtures of methyl 2-, 3-, and 4-pentenoate (MP) in over 95 %selectivity,containing asurprising 81 %of M4P.This process allows the application of aselective hydroformylation to this mixture to convert M4P into methyl 5formyl-valerate (M5FV) with 90 %s electivity.T he other isomers remain unreacted. Reductive amination of M5FV and ring-closure to e-caprolactam in excellent yield had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…40,41 Hydroformylation products such as methyl 5-formylpentanoate and methyl 6-hydroxyhexanoate are of great interest as monomers for the synthesis of polyamides and poly(hydroxyalkanoates) (PHAs), which are important biodegradable polymers. 42,43…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Hydroformylation products such as methyl 5-formylpentanoate and methyl 6-hydroxyhexanoate are of great interest as monomers for the synthesis of polyamides and poly(hydroxyalkanoates) (PHAs), which are important biodegradable polymers. 42,43…”
Section: ■ Introductionmentioning
confidence: 99%
“…Electron-donating substituents favor reductive hydroformylation to alcohols, while electron-withdrawing substituents favor alkoxycarbonylation to give ester products. Furthermore, hydroformylation of the functionalized alkenes methyl 4-pentenoate and methyl 2-pentenoate has been investigated. ,, These substrates can be prepared from the methoxycarbonylation of C4 feedstocks or from renewable sources such as unsaturated fatty esters or γ-valerolactone (GVL). , Hydroformylation products such as methyl 5-formylpentanoate and methyl 6-hydroxyhexanoate are of great interest as monomers for the synthesis of polyamides and poly­(hydroxyalkanoates) (PHAs), which are important biodegradable polymers. , …”
Section: Introductionmentioning
confidence: 99%
“…24 The most studied and used ones are aminolevulinic acid (herbicide), 2-methyl tetrahydrofuran (solvent and fuel), 25,26 γ-valerolactone 27 (solvent), ester derivatives ( plasticisers, fragrances and fuels), [28][29][30] and the nylon intermediates adipic acid and caprolactam. [31][32][33][34][35][36][37] LA can be converted into methyl vinyl ketone (monomer, vitamin A precursor) under oxidative conditions, 38 or via decarbonylation of the intermediate angelica lactone. 39,40 There are three isomers of angelica lactone (α-AL, β-AL, and γ-AL) which are shown in Scheme 1a.…”
Section: Introductionmentioning
confidence: 99%
“…128,129 Butenes have drop-in potential in polyolefin process streams. 136−142 This GVL-to-butenes decarboxylation route also can be modified to produce adipic acid 62,125,131 and ε-caprolactam, 126,127,130,131 both of which are commercially relevant in the production of polyamides (e.g., nylon-6 and nylon-6,6, respectively). Finally, new materials derived from the LevA/GVL platform have been reported, including high-T g (>200 °C) α-methylene-γ-valerolactone (MGVL)-based polymers 135 and related polyurethanes.…”
mentioning
confidence: 99%
“…LevA and GVL are functionally simpler than the compound classes described earlier and, as a result, are precursors to monomers that are typically derived from petroleum. , LevA is generated through the continued acid-catalyzed transformation of furans, especially HMF, , and formation of GVL from LevA requires an additional reductive catalytic step typically accomplished with a supported ruthenium catalyst. , Several schemes have been developed that use LevA or GVL as starting materials for the synthesis of drop-in replacements to petrochemical monomers. For example, Bond et al demonstrated that butenes can be generated from GVL in high yields (>90% of theoretical molar yield) through catalytic decarboxylation. , Butenes have drop-in potential in polyolefin process streams. This GVL-to-butenes decarboxylation route also can be modified to produce adipic acid ,, and ε-caprolactam, ,,, both of which are commercially relevant in the production of polyamides (e.g., nylon-6 and nylon-6,6, respectively). Finally, new materials derived from the LevA/GVL platform have been reported, including high- T g (>200 °C) α-methylene-γ-valerolactone (MGVL)-based polymers and related polyurethanes. , …”
mentioning
confidence: 99%